Effect of the Grain Boundary Microstructure on SCC Resistance of High Strength Al-Zn-Mg Alloy Extruded Materials - Tomoo Yoshida; Seungwon Lee; Taiki Tsuchiya; Satoshi Murakami; Kenji Matsuda (Archives of Metallurgy and Materials, 2025)
It is known while Al-Zn-Mg alloys extruded materials have high strength, those materials are characteristically occurred to Stress Corrosion Cracking (SCC). Our group have systematically controlled Mg and Zn composition and clarified the relationship between strength and precipitates. The purpose of this study is to clarify the relationship between the mechanical properties and SCC resistance and the microstructure. Therefore, our group controlled the mechanical properties and SCC resistance by adjusting the chemical composition and the quenching conditions of our Al-Zn-Mg alloy extruded materials, and the following two findings were obtained by using SCC test, tensile test, and transmission electron microscope (TEM) observation. The number density of η' phase on Al-Zn-Mg alloy extruded materials affected the improvement of mechanical properties, and the precipitation free zone (PFZ), which is the grain boundary microstructure affected SCC resistance.